Extraskeletal osteosarcoma: A large series treated at a single institution. (30th January 2018) - Wang, Haotong; Miao, Ruoyu; Jacobson, Alex; Harmon, David; Choy, Edwin; Hornicek, Francis; Raskin, Kevin; Chebib, Ivan; DeLaney, Thomas F; Chen, Yen-Lin E
Purpose: This study is to present a large cohort of extraskeletal osteosarcoma (ESOS) and evaluate prognostic factors and treatment options.Methods: Medical records were reviewed retrospectively for 41 patients with extraskeletal osteosarcoma that was diagnosed by pathology, and treated at our institution between 1960 and 2016. Kaplan-Meier analysis and Cox proportional hazards regression were used to identify variables that affect survival outcomes.Results: 41 patients were identified from 952 osteosarcomas. 32 patients had non-metastatic disease. Prognostic factors were identified by univariate analysis and multi-variate analysis. Surgery ( p <0.001), and surgery type ( p <0.001) both were shown to significantly affect overall survival (OS). Chemotherapy and radiation therapy (RT) did not show any significant effect on OS, local recurrence, or progression free survival as a whole. However for patients who had incomplete resection with residual tumor RT improved OS ( p =0.03). The survival curve for ESOS follows more closely that of non-rhabdomyosarcoma soft tissue sarcomas (NRSTS).Conclusions: ESOS is a very rare tumor. Attempt to achieve wide resection is the treatment of choice. However for patients who are not able to achieve complete resection, RT may improve OS. The behavior of ESOS more closely follows that of NRSTS than osteosarcoma of the bone.